2020
DOI: 10.3390/rs12193119
|View full text |Cite
|
Sign up to set email alerts
|

Crop Classification Method Based on Optimal Feature Selection and Hybrid CNN-RF Networks for Multi-Temporal Remote Sensing Imagery

Abstract: Although efforts and progress have been made in crop classification using optical remote sensing images, it is still necessary to make full use of the high spatial, temporal, and spectral resolutions of remote sensing images. However, with the increasing volume of remote sensing data, a key emerging issue in the field of crop classification is how to find useful information from massive data to balance classification accuracy and processing time. To address this challenge, we developed a novel crop classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 51 publications
(31 reference statements)
2
31
0
3
Order By: Relevance
“…The vegetation index can mitigate the effects of the atmosphere, terrain, and thin clouds [ 52 , 53 ]. Some studies also demonstrated that spatial features such as texture information could effectively improve extraction accuracy when using mono-temporal images [ 54 , 55 ]. However, because this study focused on which band and which bands combination were more effective for garlic extraction, no additional features were used.…”
Section: Discussionmentioning
confidence: 99%
“…The vegetation index can mitigate the effects of the atmosphere, terrain, and thin clouds [ 52 , 53 ]. Some studies also demonstrated that spatial features such as texture information could effectively improve extraction accuracy when using mono-temporal images [ 54 , 55 ]. However, because this study focused on which band and which bands combination were more effective for garlic extraction, no additional features were used.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of classification with limited inputs can be improved by applying a hybrid model with multiple classifiers where each individual classifier exhibits complementary behavior [34][35][36]. The combination of the DL model with the ML model can achieve better classification accuracy than each single model.…”
Section: Introductionmentioning
confidence: 99%
“…Such a hybrid model combining a CNN as a feature extractor with RF as a sophisticated classifier (herein referred to as CNN-RF) has been proposed for the supervised classification. Moreover, its effectiveness when insufficient information is used for the learning process is demonstrated, compared with conventional CNN that is susceptible to overfitting problems due to input information deficiency [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For different classification targets, the accuracy will be different by using spectral features, texture features, or a combination of multiple features at different times [30]. More and more researchers combine multiple features [20,31,32] of multi-temporal images [33][34][35][36] to improve classification accuracy.…”
Section: Introductionmentioning
confidence: 99%